Summary of energy demand and renewable energy policies in Malaysia. (January 2016) - Bujang, A.S.; Bern, C.J.; Brumm, T.J.
Abstract: Malaysia is a 'newly-industrialized' country that relies heavily on its exports of oil and is a major producer of palm oil and rubber. Due to favorable geographical attributes, renewable resources such as hydroelectric, solar and biomass provides attractive alternatives to dependence on fossil fuels. Fuel diversification policies were introduced in 1999 to promote the use of renewable energy, particularly in electricity generation. Diversification of energy resources are one of the main pillars in the new Malaysia plan. Other than hydroelectric and solar energy, biomass from palm oil and other agricultural practices including fruit crops can be utilized to produce energy and renewable resources. Although existing policies point towards integration of sustainable energy resources, a more aggressive approach is needed to substantially offset fossil-fuel consumption.